PENGARUH FINGER PAINTING TERHADAP PERKEMBANGAN MOTORIK HALUS ANAK USIA PRASEKOLAH DI TK SARTIKA I SUMURGENUK KECAMATAN BABAT LAMONGAN - Maghfuroh, Lilis; Chayaning Putri, Kiki (Unusa Press, 2017)
Preschoolers are children aged between 3-6 years. In this age, children are undergoing the process of growth and development that is very rapid and important for the process of further developments. In the initial survey, it was obtained a few preschool children experiencing fine motor development suspect. The purpose of this study was to determine the effect of finger painting on fine motor development of preschool children in Sartika 1 Sumurgenuk kindergarten Babat Lamongan. This study used a pre-experimental design with the approach of one-group pre-post test design and statistical analysis procedures using the Wilcoxon Sign Rank Test with significance level of p<0.05 using SPSS 16.0. The population was all preschoolers in Sartika 1 Sumurgenuk kindergarten Babat Lamongan as many as 47 children and the sample was 42 children. The results showed that almost all children have normal fine motor development after being given finger painting, with a value of p = 0.001 where p><0.05, H1 was accepted meaning that there was influence of finger painting on the development of fine motor skills of preschoolers in Sartika 1 Sumurgenuk kindergarten Babat Lamongan. It is hope that the educators of preschoolers can suggest finger painting activities as a method to develop and improve fine motor development of children. Keywords: Finger painting, fine motor development, Preschool Children.> <0.05 using SPSS 16.0. The population was all preschoolers in Sartika 1 Sumurgenuk kindergarten Babat Lamongan as many as 47 children and the sample was 42 children. The results showed that almost all children have normal fine motor development after being given finger painting, with a value of p = 0.001 where p<0.05, H1 was accepted meaning that there was influence of finger painting on the development of fine motor skills of preschoolers in Sartika 1 Sumurgenuk kindergarten Babat Lamongan. It is hope that the educators of preschoolers can suggest finger painting activities as a method to develop and improve fine motor development of children.   Keywords: Finger painting, fine motor development, Preschool Children.